Sustainable Leaching of Cu, Ni, and Au from Waste Printed Circuit Boards Using Choline Chloride-Based Deep Eutectic Solvents - Sara Saffaj; Diego Mantovani; Georgios Kolliopoulos (Metals)
Electronic waste (e-waste) is becoming a serious problem that impacts the environment due to its fast-growing volume. This rise is linked to high electronic and electrical equipment production to meet the increasing demand for high-end electronic devices. Conventional e-waste recycling approaches, including hydrometallurgy and pyrometallurgy, often involve substantial water and energy consumption and the generation of by-products, such as the emission of toxic gases or hazardous effluents. Within this context, solvometallurgy has emerged as a compelling alternative, whereby green non-toxic non-aqueous solvents, namely deep eutectic solvents (DESs), are used to extract and recover the metals with minimal water and harsh acid/base chemical use. The current study presents the solvo-leaching results of critical and strategic metals, i.e., copper (Cu) and nickel (Ni), and precious metals, i.e., gold (Au), from waste printed circuit boards (PCBs). Five different DESs were tested at mild conditions, namely at a temperature of 65 °C, a stirring speed of 300 rpm, a solid/liquid ratio of 10 g/L, and in the presence of iodine (I2) for 96 h. Among the different solvents tested, the one consisting of choline chloride (ChCl), acetic acid (AA), and I2 emerged as the optimal solvent, leading to the selective extraction of 99% of Cu, 92% of Ni, and 90% of Au from the PCB powder.